Polyclonal RB1 mutations and acquired resistance to CDK 4/6 inhibitors in patients with metastatic breast cancer. (11th December 2017) - Condorelli, R; Spring, L; O'Shaughnessy, J; Lacroix, L; Bailleux, C; Scott, V; Dubois, J; Nagy, R J; Lanman, R B; Iafrate, A J; Andre, F; Bardia, A
Abstract: Background: While deregulation of the cyclin D1-CDK4/6-retinoblastoma pathway is common in hormone receptor positive (HR+) breast cancer, Rb is usually intact in HR+ breast cancer, and targeted CDK 4/6 inhibitors that act upstream of Rb, are routinely being utilized in clinical practice. However, factors that can lead to clinical resistance to CDK 4/6 inhibitors are not known. Patients and methods: We identified patients who had pre- and post-genotyping in tissue and peripheral blood samples after receiving CDK 4/6 inhibitors. Genotyping was carried out in tumor tissue or blood collected before start of CDK 4/6 inhibitor and after disease progression on CDK 4/6 inhibitor, covering more than 90% of the coding region in RB1 . Results: We identified detectable acquired RB1 mutations in circulating tumor DNA (ctDNA) after exposure to CDK4/6 inhibitor (palbociclib, palbociclib, ribociclib) for 5, 8, and 13 months, respectively, in three patients. The RB1 mutations included substitution in donor splicing site of exon 8 of the RB1 gene in patient #1; substitution in donor splicing site of exon 22 of RB1 gene, exon 19 deletion, exon 3 insertion in patient #2; and RB1 exon 16 H483Y mutation in patient #3. None of these RB1 mutations were present in the pre-CDK 4/6 specimen highlighting these molecular alterations, which lead to functional loss of Rb1, likely emerged under selective pressure from the CDK4/6 inhibitor potentially confering therapeutic resistance. Conclusion: This is the first clinical report to describe the emergence of somatic RB1 mutations after exposure to palbociclib or ribociclib, in patients with metastatic breast cancer. Further research is needed to validate these findings, identify how these mutations temporally emerge under selective pressure of CDK 4/6 inhibitor, and develop rational therapeutic strategies.